The comparative cranial osteology of the South African Lacertilia (Reptilia : Squamata) - Van den Worm, Johan H.(Johan Heinrich) (Stellenbosch : Stellenbosch University, 2012)
Thesis (M. Sc.) -- University of Stellenbosch, 1998.